Kisah Ashabul Kahfi: Studi Perbandingan Tafsir Al-Misbah dan Tafsir Ibnu Katsir - Muliawann, Juan; Aulia, Widad; Hakim, Luqman Nul (Pubmedia Social Sciences and Humanities, 2024)
The story is one of the five main contents of the Qur'an, and the stories in the Qur'an are unique and extraordinary. This research will delve into one of the Qur'anic stories, namely the story of Ashabul Kahfi in Surah Al-Kahfi verses 9-26, and compare it with two exegesis books: "Al-Misbah" by M. Quraish Shihab and the exegesis of Ibn Kathir on Ibn Kathir. Literary analysis will examine the story of Ashabul Kahfi according to M. Quraish Shihab and Ibn Kathir. Comparing the two exegesis texts of the Ashabul Kahfi story will reveal similarities and differences. Furthermore, the conclusions drawn from both interpretations can be applied to modern Indonesian culture. Like previous stories, this narrative provides a positive example for young people, as Ashabul Kahfi were motivated youths who left their community for their beliefs. They sought forgiveness and salvation from Allah, who led them to a cave, caused them to sleep for 309 years, and woke them without aging.